First case report of systemic cat-scratch disease (Bartonella henselae) in Peru - Polanco Aguilar, Pablo Manuel (2018)
Introduction: Cat-scratch disease most of the times is described reporting its typical form; systemic forms are rare and they are seldom reported. Cat-scratch disease may have a great variety of presentations, and some of them are quite unusual. This is the very first time that the systemic form is reported in Peru.Clinical case: We present two girls, 5 and 6 years old, hospitalized in the pediatric ward of Hospital Nacional Carlos Alberto Seguin, EsSalud, Arequipa, Peru, who presented with the systemic form of cat scratch disease. Both girls were scratched by kittens without developing a characteristic local reaction, and they presented with prolonged fever, malaise, anorexia, headache, abdominal pain, lymph node enlargement, liver and spleen involvement, accelerated erythrocyte sedimentation rate, high levels of C-reactive protein, leukocytosis, left shift, slightly elevated or normal liver enzymes; and in both girls the diagnosis was confirmed with a positive result in serological testing (IgG and IgM) for Bartonella henselae. Also, some splenic microabscesses were found in the CT scan. Both girls responded to antimicrobial therapy using a macrolide combined with rifampin for one month.